2002
DOI: 10.1111/j.1748-8583.2002.tb00068.x
|View full text |Cite
|
Sign up to set email alerts
|

Small firms and internationalisation: learning to manage and managing to learn

Abstract: Small firms contribute significantly to the UK economy, but most research into learning and work features the experience of large organisations. This article focuses on learning and work in small organisations. An interpretive framework relating to organisational learning is derived from the literature. Data on learning in small firms that internationalise are analysed to assess the extent to which models of organisational learning are applicable to the context and challenges they face. The article suggests th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
1
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 43 publications
1
71
1
5
Order By: Relevance
“…In addition, there is an increasing demand for expatriate employees in a far wider range of organizations than the traditional large MNC partly due to the rapid growth of small and medium enterprise (SME) internationalization (Anderson and Boocock, 2002) and international joint ventures (IJVs) . Recent research highlights the importance of staffing and the top management team's international experience to the performance of international SMEs (Monks and Scullion, 2001).…”
Section: Demand Side Issuesmentioning
confidence: 99%
“…In addition, there is an increasing demand for expatriate employees in a far wider range of organizations than the traditional large MNC partly due to the rapid growth of small and medium enterprise (SME) internationalization (Anderson and Boocock, 2002) and international joint ventures (IJVs) . Recent research highlights the importance of staffing and the top management team's international experience to the performance of international SMEs (Monks and Scullion, 2001).…”
Section: Demand Side Issuesmentioning
confidence: 99%
“…The formation, and re-formation, of self-organizing and informal innovation networks is central to this article, not least because reliance on informal networks is particularly important in the early stages of creating and developing a business (Anderson and Boocock, 2002) such as the HduV project. Furthermore, these networks can bring together people with different types of tacit knowledge, facilitating creativity (Dovey, 2009) which, together with social capital, are important elements in the HduV story.…”
Section: Self-organizing Innovation Network and The Role Of Social Cmentioning
confidence: 99%
“…Amongst these studies a tension is identified between the preference by small firms for learning through informal social and network contacts and by experience (Anderson and Boocock, 2002), against the benefits reported of knowledge transfer through institutional support such as business incubation or training provision (for example, Bell et al, 1992;Weinstein et al, 1992;Jones and Craven, 2001;Pena, 2002;Collinson and Gregson, 2003;Chrisman and McMullan, 2004). Moreover, there are some who argue that the nature of assistance must recognise that some firms are more able to respond to assistance than others.…”
Section: Network: As a Learning Resourcementioning
confidence: 99%